2020
DOI: 10.2147/dddt.s258187
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Galangin Improved Non-Alcoholic Fatty Liver Disease in Mice by Promoting Autophagy</p>

Abstract: Background: Previous studies have shown that curcumin derivatives can improve the fatty degeneration of liver tissue that occurs in nonalcoholic fatty liver disease (NAFLD). However, the specific mechanism for that improvement remains unclear. We examined whether the curcumin derivative galangin could reduce the fatty degeneration of liver tissue in mice with NAFLD by inducing autophagy, from the perspective of both prevention and treatment. Methods: C57BL/6J mice were randomly assigned to a prevention group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 42 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…Galangin which is one of the polyphenols in poplar propolis suppresses hepatic inflammation and oxidative damage through the activation of nuclear factor erythroid 2‐related factor 2 (Nrf‐2) (Sanyal et al, 2010). Prior studies showed that galangin not only attenuates hepatic steatosis via promoting hepatocyte autophagy (Zhang et al, 2020), but also inhibits HSCs proliferation and collagen gene expression via inhibiting TGF‐β expression (Wang et al, 2013). Propolin G is another polyphenols in propolis that were shown to down‐regulate collagen gene expression through eliminating JNK and TGF‐β/Smad signaling pathways, stimulating apoptosis‐related protein expression, and inhibiting proliferation in the HSCs treated with TGF‐β (Su et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Galangin which is one of the polyphenols in poplar propolis suppresses hepatic inflammation and oxidative damage through the activation of nuclear factor erythroid 2‐related factor 2 (Nrf‐2) (Sanyal et al, 2010). Prior studies showed that galangin not only attenuates hepatic steatosis via promoting hepatocyte autophagy (Zhang et al, 2020), but also inhibits HSCs proliferation and collagen gene expression via inhibiting TGF‐β expression (Wang et al, 2013). Propolin G is another polyphenols in propolis that were shown to down‐regulate collagen gene expression through eliminating JNK and TGF‐β/Smad signaling pathways, stimulating apoptosis‐related protein expression, and inhibiting proliferation in the HSCs treated with TGF‐β (Su et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Galangin which is one of the polyphenols in poplar propolis suppresses hepatic inflammation and oxidative damage through the activation of nuclear factor erythroid 2-related factor 2 (Nrf-2) (Sanyal et al, 2010). Prior studies showed that galangin not only attenuates hepatic steatosis via promoting hepatocyte autophagy (Zhang et al, 2020), but also inhibits HSCs proliferation and collagen gene expression via inhibiting TGF-β expression (Wang et al, 2013).…”
Section: F I G U R Ementioning
confidence: 99%
“…ω-3 fatty acids present in fish oil, flaxseeds, and walnuts prevent FFA-induced lipotoxicity through induction of autophagy in NAFLD [ 105 ]. Similarly, widely used components in Indian traditional medicine, curcumin and its derivatives have shown protective effects in animal models of NAFLD by an autophagy-mediated pathway [ 106 ].…”
Section: Pharmacological and Nonpharmacological Inducers Of Autophagy...mentioning
confidence: 99%
“…Zhang et al reported that galangin alleviated hepatic steatosis through regulating the expressions of becline1, LC3-II/LC3-I, Atg3, AMPKα1, and decreased mTOR protein expression to promote hepatocyte autophagy in NAFLD mice (Zhang et al, 2020).…”
Section: Other Diseasesmentioning
confidence: 99%